Emergency triage - Mackway-Jones, Kevin; Marsden, Janet; Windle, Jill.; Harris, Nathan; Manchester Triage Group; Advanced Life Support Group (Manchester, England) (Chichester, England : Wiley-Blackwell, 2014)
The Manchester Triage System (MTS) is the most widely used triage system in the UK, Europe and Australia, with tens of millions of patients being processed through hospital emergency departments. It is also used in hospitals throughout Brazil. Emergency Triage is the core text for the MTS, which utilises a risk averse system of prioritisation for patients in all unscheduled care settings. As such, it is an essential text for all emergency department staff using the MTS, in particular triage nurses. The book is both a training tool and a reference for daily use in the Emergency.
The decision-making process and triage -- The triage method -- Pain assessment as part of the triage process -- Patient management, triage and the triage practitioner -- Auditing the triage process -- Telephone triage -- Beyond prioritisation.
Includes index.
Description based on print version record.
Keywords: Triage (Medicine); Emergency nursing; Hospitals -- Emergency services; Emergency nursing; Hospitals -- Emergency services; Triage (Medicine); Electronic books; Electronic books